2018
DOI: 10.1016/j.energy.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of cashew nutshells: Characterization of products and energy balance

Abstract: Cashew cultivation leads to the generation of large amounts of nutshells. In order to determine whether pyrolysis could be a suitable method for the valorization of this agricultural residue, cashew nutshells (CNS) from Burkina Faso were pyrolyzed in the temperature range between 400 and 600 ºC in a laboratory-scale fixed bed reactor. The solid, liquid and gaseous fractions were quantified and characterized, with special focus on the solid product. Recovery of the cashew nutshell liquid (CNSL) was accomplished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 32 publications
1
21
0
1
Order By: Relevance
“…The highest decomposition rate on the DTG profile was 0.57 mg/min and 0.56 mg/min as observed at about 261.2℃ and 340.3℃ respectively that indicating a broad peak. DTG peak of CNS also reported in a range of 250-400℃ in a conventional pyrolysis [29,30]. Some partial evaporation take place at temperature higher than 300 o C and it is assumed due to the high boiling point of liquid in CNS compound.…”
Section: Resultsmentioning
confidence: 82%
“…The highest decomposition rate on the DTG profile was 0.57 mg/min and 0.56 mg/min as observed at about 261.2℃ and 340.3℃ respectively that indicating a broad peak. DTG peak of CNS also reported in a range of 250-400℃ in a conventional pyrolysis [29,30]. Some partial evaporation take place at temperature higher than 300 o C and it is assumed due to the high boiling point of liquid in CNS compound.…”
Section: Resultsmentioning
confidence: 82%
“…The effect of the temperature from 400 to 900 o C on the CNS char characteristics was pointed out in the literature. [12] An increase in temperature was directly proportional to the ash content, fixed-carbon and heating value of the char while the volatile matters decreased. However, the CNS char properties were observed as no significant change after 500 o C. Besides, the behaviors of CNS were differing from the most of woody biomass pyrolysis with the different overlapping loss peaks of hemicellulose, cellulose and lignin decompositions.…”
Section: Introductionmentioning
confidence: 96%
“…The pyrolysis conditions of biomass, for example, pyrolysis temperature, heating rate or residence time have shown great influences on characteristics of the char produced (ash content, volatile matter, fixed carbon content, and heating value) and their usages. [8][9][10][11][12] Since CNS is an uncommon feedstock for pyrolysis, only few studies on thermal behaviors of CNS during pyrolysis have been reported. The effect of the temperature from 400 to 900 o C on the CNS char characteristics was pointed out in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The agroindustrial crop's valorization is interesting for synthetic chemistry, perfumery, cosmetics, biomedicine, and energy industries. Some studies reported techno‐economic valorization of nutshells residues, such as, macadamia, 3–9 pistachio, 10,11 pecan, 12–17 almond, 18 cashew, 19–21 cedar, 22 oak, 23 fox 24 for catalytic pyrolysis, wastewater treatment, bio‐fillers in a polymeric matrix, microporous sorbents, preparation of carbon‐based products, biochar, supercapacitor for powering electronic devices.…”
Section: Introductionmentioning
confidence: 99%